Immunohistochemical Evidence from APP-Transgenic Mice for Glutaminyl Cyclase as Drug Target to Diminish pE-Abeta Formation - Maike Hartlage-Rübsamen; Alexandra Bluhm; Anke Piechotta; Miriam Linnert; Jens-Ulrich Rahfeld; Hans-Ulrich Demuth; Inge Lues; Peer-Hendrik Kuhn; Stefan F. Lichtenthaler; Steffen Roßner; Corinna Höfling (Molecules, 2018)
Oligomeric assemblies of neurotoxic amyloid beta (Abeta) peptides generated by proteolytical processing of the amyloid precursor protein (APP) play a key role in the pathogenesis of Alzheimer’s disease (AD). In recent years, a substantial heterogeneity of Abeta peptides with distinct biophysical and cell biological properties has been demonstrated. Among these, a particularly neurotoxic and disease-specific Abeta variant is N-terminally truncated and modified to pyroglutamate (pE-Abeta). Cell biological and animal experimental studies imply the catalysis of this modification by the enzyme glutaminyl cyclase (QC). However, direct histopathological evidence in transgenic animals from comparative brain region and cell type-specific expression of transgenic hAPP and QC, on the one hand, and on the formation of pE-Abeta aggregates, on the other, is lacking. Here, using single light microscopic, as well as triple immunofluorescent, labeling, we report the deposition of pE-Abeta only in the brain regions of APP-transgenic Tg2576 mice with detectable human APP and endogenous QC expression, such as the hippocampus, piriform cortex, and amygdala. Brain regions showing human APP expression without the concomitant presence of QC (the anterodorsal thalamic nucleus and perifornical nucleus) do not display pE-Abeta plaque formation. However, we also identified brain regions with substantial expression of human APP and QC in the absence of pE-Abeta deposition (the Edinger-Westphal nucleus and locus coeruleus). In these brain regions, the enzymes required to generate N-truncated Abeta peptides as substrates for QC might be lacking. Our observations provide additional evidence for an involvement of QC in AD pathogenesis via QC-catalyzed pE-Abeta formation.